2023
DOI: 10.1021/acs.analchem.2c05708
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Intracellular Esterase Activity Using Ratiometric Raman Sensing and Spectral Phasor Analysis

Abstract: Carboxylesterases (CEs) are a class of enzymes that catalyze the hydrolysis of esters in a variety of endogenous and exogenous molecules. CEs play an important role in drug metabolism, in the onset and progression of disease, and can be harnessed for prodrug activation strategies. As such, the regulation of CEs is an important clinical and pharmaceutical consideration. Here, we report the first ratiometric sensor for CE activity using Raman spectroscopy based on a bisarylbutadiyne scaffold. The sensor was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For instance, Bae et al recently utilized an aryl-diyne-based Raman tag called TPP–BDDBPDM (Figure , Table S1) to develop a quantitative model to link mitochondrial membrane potential, a key indicator for mitochondria-mediated metabolic activities, with key pharmacokinetic properties (such as uptake rate and intracellular concentrations of TPP) in live cells . Taking advantage of the narrow line width of the Raman bands (<20 cm –1 ), Raman sensors for the detection of intracellular environments such as pH, ions, , small signaling molecules such as hydrogen sulfide, as well as enzymatic activity have also been developed.…”
Section: Single-cell Metabolic Profiling Using (Un)targeted Imagingmentioning
confidence: 99%
“…For instance, Bae et al recently utilized an aryl-diyne-based Raman tag called TPP–BDDBPDM (Figure , Table S1) to develop a quantitative model to link mitochondrial membrane potential, a key indicator for mitochondria-mediated metabolic activities, with key pharmacokinetic properties (such as uptake rate and intracellular concentrations of TPP) in live cells . Taking advantage of the narrow line width of the Raman bands (<20 cm –1 ), Raman sensors for the detection of intracellular environments such as pH, ions, , small signaling molecules such as hydrogen sulfide, as well as enzymatic activity have also been developed.…”
Section: Single-cell Metabolic Profiling Using (Un)targeted Imagingmentioning
confidence: 99%
“…For example, (1) Luo and co-workers showed that the CC bonds in polydiacetylene poly­(deca-4,6-diynedioic acid), which is water-soluble and functionalizable, exhibit significantly enhanced (up to ca. 10 4 fold) Raman intensity compared to conventional alkyne Raman probes and, hence, can be used for high-quality live-cell SRS imaging; (2) Potma and co-workers demonstrated that a sulfur linker can significantly improve the performance of several alkyne-based Raman probes in SRS imagining applications; (3) Fujita and co-workers utilized gold nanoparticles accumulated in the lysosome of live cells to enhance the Raman signals of colocalized alkyne-tagged drug-like molecules; (4) Ji and co-workers achieved photoswitch ability in SRS spectroscopy and microscopy by introducing alkyne-based Raman probes into the photochromic diarylethene (DTE) and demonstrated the biological utility of this technique in live cell imaging through an intracellular pulse-chase experiment; (5) Tomkinson and co-workers developed a series of low molecular weight oligoyne compounds, the alkyne stretching frequencies of which exhibit a dependence on pH, as intracellular Raman pH sensors, as well as an alkyne-based ratiometric Raman sensor for intracellular imaging of esterase activity using SRS microscopy; and (6) Evans and co-workers demonstrated the potential utility of DC473, a photosensitizer with two alkyne groups, for the study of time-dependent single-cell pharmacodynamics.…”
Section: Application Of Cc Stretching Vibration In Biological Sciencementioning
confidence: 99%
“…Ratiometric usage of materials properties, be they electrochemical, electronic, optical, or even combinational, has seen strong growth in the development of accurate techniques (Supporting Information Table S1). By simultaneous comparison of the parameters from a biological event, ratiometric measurements have been preferred since they could mitigate the environmental impacts and enable more precise detection especially within complex samples . To date, various techniques, e.g., fluorescence, resonance light scattering, Raman, bioluminescence, electrochemistry, and ECL, have been utilized in a ratiometric manner.…”
Section: Introductionmentioning
confidence: 99%